Loyalitas Pelanggan Skintific Solo Raya: Pengaruh Brand Image, Promosi dan Kepuasan Pelanggan - Fani Anisa Rahmawati; Esti Dwi Rahmawati; Indra Hastuti (Jurnal Pemimpin Bisnis Inovatif, 2024)
This research aims to analyze the mediating role of customer satisfaction on the influence of brand image and promotion on customer loyalty among users of skintific skincare products in Solo Raya. The population in this study were all users of skintific skincare products in Solo Raya who had used skintific products for at least the last 6 months and the total sample in this study was 96 respondents. The variables used in this research are brand image, promotion, customer satisfaction, and customer loyalty. The data used in this research is primary data. The data collection method used was a questionnaire. The data analysis technique used was Structural Equation Modeling-Partial Least Square (SEM-PLS) and the SmartPLS 4.0 program. The results of this research show that brand image and promotion have a positive and significant effect on customer satisfaction, brand image has a positive and significant effect on customer loyalty, promotion has no significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, customer satisfaction is able to mediate The influence of brand image on customer loyalty and customer satisfaction are not able to mediate the influence of promotions on customer loyalty.